Family welfare and the Great Recession - Julie L. Hotchkiss; Robert E. Moore; Fernando Rios-Avila (Federal Reserve Bank of Atlanta, 2014)
The analysis in this paper provides estimates of family welfare losses generated by wage and nonlabor income declines experienced across the Great Recession and by labor market constraints existing postrecession. Welfare losses are greater as families (both married and single) move up the income distribution. Total static welfare losses are estimated to amount to roughly 190 billion, comparing family welfare between 2007 and 2011.
Keywords: I30; J22; D19; E32; 330; family welfare; joint labor supply; microsimulation; constrained hours